2019
DOI: 10.1108/tpm-11-2017-0069
|View full text |Cite
|
Sign up to set email alerts
|

“You have got a friend”

Abstract: Purpose As a way to enable employees to work distantly, teleworking has gained a growing interest in companies. At the same time, management challenges regarding the teleworkers’ risk of isolation, coupled with the need to maintain cohesion for the dispersed team, to give an example, are various. How can management practices help to maintain adequate levels of perceived proximity for a dispersed team’s members? The purpose of this paper is to answer this question. Referring to a particular person’s perception … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 62 publications
0
23
0
Order By: Relevance
“…Teleworking, working from a distance [63], consists of carrying out work in a place distant from the central or production buildings, where workers do not have physical interaction with their co-workers, but rather communicate with them electronically [64]. In this sense, mobile work based on new technologies has been emerging as smaller and medium-sized wireless devices such as laptops and mobile phones allow employees to work not only from home, but practically from any location where they need to do so [65], making telecommuting a popular and growing alternative to the traditional work style [66].…”
Section: Increase In Teleworking and Its Implications On Worker Healthmentioning
confidence: 99%
“…Teleworking, working from a distance [63], consists of carrying out work in a place distant from the central or production buildings, where workers do not have physical interaction with their co-workers, but rather communicate with them electronically [64]. In this sense, mobile work based on new technologies has been emerging as smaller and medium-sized wireless devices such as laptops and mobile phones allow employees to work not only from home, but practically from any location where they need to do so [65], making telecommuting a popular and growing alternative to the traditional work style [66].…”
Section: Increase In Teleworking and Its Implications On Worker Healthmentioning
confidence: 99%
“…Certainly, the quality of communication and high identification with one's team seem intuitive enough to influence perceived proximity, and existing empirical studies have validated their relevance for both collocated and virtual teams (Kidron et al, 2016;Lähdesmäki et al, 2019;O'Leary et al, 2014;Ruiller et al, 2019). Yet, little is known how these can be practically achieved or what is the influence of other factors, such as organisational ones, on perceived proximity.…”
Section: Perceived Proximitymentioning
confidence: 99%
“…Yet, little is known how these can be practically achieved or what is the influence of other factors, such as organisational ones, on perceived proximity. Notable exceptions include two studies showing that the management style can both facilitate and hinder team interactions (Eisenberg & Krishnan, 2018;Makarius & Larson, 2017), and research by Ruiller et al (2019) who explore how management practices can facilitate perceived proximity, and investigate leadership aspects towards supporting virtual teams' in forming a shared identity.…”
Section: Perceived Proximitymentioning
confidence: 99%
“…High-perceived proximity in MNVTs indicates a feeling of closeness within the team, which is distinctly different from the actual physical distance between team members (Dekker et al, 2015; Magnusson et al, 2014; Wilson et al, 2008). Moreover, scholars have found that a sense of collective shared identity facilitates communication and information sharing among MNVT members (Kearney & Gebert, 2009) and that the higher level of communication enhances perceived proximity within these teams (Ruiller et al, 2019).…”
Section: Theoretical Foundations and Hypothesis Developmentmentioning
confidence: 99%